L’inventario nazionale del paesaggio rurale storico. Nuovi indirizzi per la pianificazione delle aree rurali - Agnoletti, Mauro (Ri-Vista. Research for landscape architecture, 2015)
In Italy there is a great richness of rural landscapes, created by man during the centuries. Their recognition, conservation and dynamic management represent important actions to keep this heritage. The essay tells about the result of a research on historical rural landscapes led by the Ministry of Agricoltural, Food and Forestry Policies, published in 2010, that starting from the work of Sereni and Gambi, faces the theme of identification and classification of cultural-historical landscapes and defines 120 “traditional” landscapes.